If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -6 = -2(3x + -7) Reorder the terms: -6 + y = -2(3x + -7) Reorder the terms: -6 + y = -2(-7 + 3x) -6 + y = (-7 * -2 + 3x * -2) -6 + y = (14 + -6x) Solving -6 + y = 14 + -6x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + y = 14 + 6 + -6x Combine like terms: -6 + 6 = 0 0 + y = 14 + 6 + -6x y = 14 + 6 + -6x Combine like terms: 14 + 6 = 20 y = 20 + -6x Simplifying y = 20 + -6x
| (x+17)(x+9)=-3 | | 10(2+1)-3(z-2z)+12=3(z-4)+3(z-4) | | S=2xy+2yz+2xz | | 13.1936=0+x*6.08 | | 9x+5=8x+4 | | Y=3600+0.8Y | | 4(x+8)+2=-14 | | 5x-60-24=3x+6 | | 10x+21= | | 1-(1-6x)=6x+2 | | 3(2x-5)-16=20+3x | | 24y-4=20 | | 10y-[11(6-y)-2]=5y+2(7-5y) | | 3s-s= | | u/12=8/7 | | -3(x-2)-26=4(x+2) | | 44+4y-15=14y-11-2y | | 110v=I(50) | | -1y-8+6y=9+5y+1 | | (3x+20)=(6x-16).5 | | 9x=8+5 | | y-1=0.3(x+3) | | 10.5x=3.5 | | 3.5(10.5x)=x | | 3h+4=5h+2 | | T=12.95-p | | 6(-3)-8=2+9m-1 | | 6s-6s-6s-2s+5s= | | -logx=.85 | | g+-3=-1 | | -y-8+6=9+5y+1 | | 63=w(w+2) |